KELIMPAHAN COLLEMBOLA PERMUKAAN TANAH DI DAERAH PERKEBUNAN MASYARAKAT DI DESA LALOWIU KECAMATAN KONDA KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - Suriana Suriana; Amirullah Amirullah; Wahyuni Wahyuni (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2015)
The aim of this study is to know the abundance of ground surface Collembolan in plantation area at Lalowiu villlage subdistrict of Konda, South Konawe regency, province of Southeast Sulawesi. The research was done by observation a the ground and sample collection by using pitfall trap and litter trap. Trap settelment at 09.00 pm and sample collecting at 09.00 am 3 days after. Litter trap sample collection was done concurrent with pitfall trap sample collection. Extract of litter trap sampling conducting by using Berlese funnel. Result of the research show that 3 ordo which divided in 6 family and 16 genus. The highest abundance of collembola at Homidia genus 8,1 Ind/m2 and the lowest abundance at Sphaeridia genus 0,05 Ind/m2.Keywords : Collembola, , Berlese funnel, Lalowiu Village, The Abundace, Pittfall trap